Social and environmental indicators of family fish farms in the atlantic forest area in the Ribeira Valley-SP - Bueno, G. W. [UNESP]; Leonardo, A. F.G.; Machado, L. P. [UNESP]; Brande, M. R. [UNESP]; Godoy, E. M. [UNESP]; David, F. S. [UNESP] (FapUNIFESP (SciELO), 2020)
The objective of this work was to apply socioenvironmental indicators in family fish farms located in the Ribeira Valley region, Atlantic Forest area, southwest of Sao Paulo state, Brazil. Thus, we identified 84 production units. Of these, we selected 40 as sample units. Among the main characteristics identified, 32% have water depth of less than five hectares with excavated ponds in semi-intensive system, 58% use family labor and 23% report the lack of specialized technical assistance as the main problem faced. The Nile tilapia (Oreochromis niloticus) represents 57% of the species produced in monoculture or polyculture systems. Therefore, family fish farms are classified as small production systems with emphasis on the need to adapt natural resources, management capacity and efficiency of production practices. Social indicators ranged from 0.75 to 1.00 for salary equity, proportion of self-employment, use of local labor, gender inclusion and age inclusion, demonstrating the ability of aquaculture to assist local social development through job and income generation.
Indicadores de sustentabilidade socioambiental de pisciculturas familiares em área de Mata Atlântica, no Vale do Ribeira-SP
Keywords: Aquaculture extension; Bio economy; Fish farm family; Rural development; Socioenvironmental indicators